Introducing structured caregiver training in stroke care: findings from the TRACS process evaluation study. Issue 4 (15th April 2014) - Clarke, David J; Hawkins, R; Sadler, E; Harding, G; McKevitt, C; Godfrey, M; Dickerson, J; Farrin, A J; Kalra, L; Smithard, D; Forster, A
Abstract : Objective: To evaluate the process of implementation of the modified London Stroke Carers Training Course (LSCTC) in the Training Caregivers After Stroke (TRACS) cluster randomised trial and contribute to the interpretation of the TRACS trial results. The LSCTC was a structured competency-based training programme designed to help develop the knowledge and skills (eg, patient handling or transfer skills) essential for the day-to-day management of disabled survivors of stroke. The LSCTC comprised 14 components, 6 were mandatory (and delivered to all) and 8 non-mandatory, to be delivered based on individual assessment of caregiver need. Design: Process evaluation using non-participant observation, documentary analysis and semistructured interviews. Participants: Patients with stroke (n=38), caregivers (n=38), stroke unit staff (n=53). Settings: 10 of the 36 stroke units participating in the TRACS trial in four English regions (Yorkshire, North West, South East and South West, Peninsula). Results: Preparatory cascade training on delivery of the LSCTC did not reach all staff and did not lead to multidisciplinary team (MDT) wide understanding of, engagement with or commitment to the LSCTC. Although senior therapists in most intervention units observed developed ownership of the LSCTC, MDT working led to separation rather than integration of delivery of LSCTC elements. Organisational features of stroke units and professionals' patient-focused practices limited the involvement of caregivers. Caregivers were often invited to observe therapy or care being provided by professionals but had few opportunities to make sense of, or to develop knowledge and stroke-specific skills provided by the LSCTC. Where provided, caregiver training came very late in the inpatient stay. Assessment and development of caregiver competence was not commonly observed. Conclusions: Contextual factors including service improvement pressures and staff perceptions of the necessity for and work required in caregiver training impacted negatively on implementation of the caregiver training intervention. Structured caregiver training programmes such as the LSCTC are unlikely to be practical in settings with short inpatient stays. Stroke units where early supported discharge is in place potentially offer a more effective vehicle for introducing competency based caregiver training. LINKED TRACS Cluster randomised controlled trial number: ISRCTN49208824.